Related party transactions: Do they matter to auditors? Evidence from audit opinions in Indonesia - Mustikarini, Arizona (ABIS: Accounting and Business Information Systems Journal, 2025)
I examine how independent auditors respond to the firms' related party transactions (RPTs), namely related party sales, purchases, receivables, and payables. I use Indonesian data where RPTs are profoundly prevalent. I predict that the nature of RPTs potentially leads to a higher risk of material misstatements, and thus, the auditor is likely to issue a modified audit opinion (MAO). The data is hand-collected from RPT disclosures in the annual reports from 360 firm-years during the financial year of 2011-2015. The data is analyzed using a logistic regression. Based on the analyses, I find that related party sales, purchases, and payables are positively associated with the issuance of an MAO. These results suggest that auditors respond to RPTs as high-risk transactions. However, I find no empirical support that RPT receivables are associated with MAO issuance. Findings from this research contribute to the literature by demonstrating that RPTs matter to auditors’ decisions about opinion issuance. Results also suggest practical implications from this study. It is critical for auditors to have a comprehensive knowledge of the nature of RPTs conducted by audit clients, as RPTs are considered high-risk transactions.